Women, prison, & crime - Pollock, Joycelyn M.
This text takes a comprehensive look at women in America's prisons, covering the history of women's prisons, crime rates, and sentencing practices. It provides detailed descriptions of prisoner subcultures, programs, management and staff issues, and legal issues of female prisoners, while also expanding beyond U.S. soil to compare women's prisons in other countries